EMPIRICAL SELECTION OF DROUGHT TOLERANT LINES IN EARLY SEGREGATING GENERATION OF CHICKPEA DEVELOPED USING A NEW SOURCE OF DROUGHT TOLERANT GERMPLASM LINE - M. S. SHIVAKUMAR,; P. M. SALIMATH,; SUMA S. BIRADAR,; O. SRIDEVI, (The Bioscan, 2014)
Chickpea (Cicer arietinum L.) is an important food legume with 92 per cent of area and 89 per cent of the global production are concentrated in semi-arid tropical countries. The present study was conducted with objective of development of high yielding, drought tolerant lines. For this F2-3 progenies obtained from the cross ICC-13124, a drought tolerant genotype and WR-315 were evaluated separately for yield components and drought tolerance. The moisture stress was created by taking up sowing 30 days later than normal sowing and withholding irrigation 14 days after sowing on the contrary, for non-stress condition, irrigation was given at regular intervals till physiological maturity. Variability parameters were assessed for yield components and drought parameters. Among the nine quantitative characters studied, seed yield per plant was most affected by drought and exhibited 41.1% reduction followed by number of seeds per plant (33.18%) and number of pods (32.09%) under drought compared to irrigated condition. Under drought situation, most of the productivity related traits like number of pods, seeds per plant and seed yield had high heritability coupled with high GAM indicating amenability such traits for improvement of drought tolerance. About 27 F3 families had still lower drought susceptibility index (DSI), minimum tolerance to drought stress (TDS), high drought tolerance efficiency (DTE) and mean productivity than ICC 13124. The lines 389 and 491 were observed as the best tolerant line to drought stress environment under the field condition with respect to both yield and drought parameters. Such best families can be evaluated on large scale to identify variety or as a germplasm line for breeding drought tolerance and productivity.